Impact of psychological resilience and social support on psycho-social adjustment in postoperative patients with primary hepatocellular carcinoma: mediating effects of fear of progression - Li, Min; Yu, Binyang; He, Haiyan; Li, Ning; Gao, Rui (Frontiers in Psychology, 2024)
Background: Postoperative patients with primary hepatocellular carcinoma (HCC) confront not only physiological challenges but also psychological and social adaptation issues. It is imperative to enhance psycho-social adjustment (PSA) levels and further improve the quality of life among this population. However, research on PSA levels in postoperative HCC patients is lacking, and investigations into its associations with psychological resilience, social support, and fear of progression (FoP) remain unexplored currently.Objectives: This study aims to: 1) investigate the current status of PSA and analyze its influencing factors among postoperative HCC patients; 2) explore the interrelationships among psychological resilience, social support, FoP and PSA based on the Chronic Illness Adaptation Model employing a structural equation model.Convenience sampling methods were employed to recruit participants from the Department of Hepatobiliary Surgery at a tertiary hospital in Xi'an, Shaanxi, China, and a total of 399 patients completed the surveys. The survey instruments included a general information questionnaire, Connor-Davidson Resilience Scale (CD-RISC), Social Support Rating Scale (SSRS), Fear of Progression Questionnaire-Short Form (FoP-Q-SF), and Psychosocial Adjustment to Illness Scale Self-report (PAIS-SR). Data entry was conducted using Epidata 3.1 with dual verification, followed by statistical analyses performed using SPSS 27.0 and Amos 28.0.The structural equation model revealed two paths. In Path 1 (psychological resilience → FoP → PSA), the direct effect was -0.383 (95% CI [-0.589, -0.112]), with an indirect effect of -0.075 (95% CI [-0.170, -0.018]). In Path 2 (social support → FoP → PSA), the direct effect was -0.297 (95% CI [-0.587, -0.063]), with an indirect effect of -0.069 (95% CI [-0.156, -0.019]).Postoperative patients with primary HCC exhibit lower levels of PSA. Higher levels of psychological resilience and social support correspond to elevated PSA levels. Conversely, advanced age, greater financial burden, and increased FoP are associated with lower PSA levels. FoP serves as a partial mediator between psychological resilience and PSA, as well as between social support and PSA. Future research would benefit from longitudinal designs to elucidate the developmental trajectories and causal links among these variables.